2010
DOI: 10.3945/ajcn.2009.29139
|View full text |Cite
|
Sign up to set email alerts
|

Eating vegetables first: the use of portion size to increase vegetable intake in preschool children

Abstract: Increasing the portion size of a vegetable served as a first course can be an effective strategy for increasing vegetable consumption in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 37 publications
3
100
0
3
Order By: Relevance
“…When 44 intervention arms within studies were used as the unit of analysis, a slightly higher effect size was observed g = 0.42, CI: 0.33-0.51, Z = 8.79, p < 0.001. The sensitivity analyses performed by excluding three studies (Bell et al, 2015;Harnack et al, 2012;Spill et al, 2010) …”
Section: Synthesis Of Results: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…When 44 intervention arms within studies were used as the unit of analysis, a slightly higher effect size was observed g = 0.42, CI: 0.33-0.51, Z = 8.79, p < 0.001. The sensitivity analyses performed by excluding three studies (Bell et al, 2015;Harnack et al, 2012;Spill et al, 2010) …”
Section: Synthesis Of Results: Meta-analysismentioning
confidence: 99%
“…For studies with more than one intervention group, the intervention arm (condition) was used as the unit of analysis. Sensitivity analysis was performed by excluding three studies, one which reported median data (Bell, Hendrie, Hartley, & Golley, 2015), another with various experimental conditions but none were defined as standard or control condition (Spill, Birch, Roe, & Rolls, 2010) and a third study by Harnack et al (2012) who found non-significant effects for one of their intervention arm but did not report the precise p value (p value of > 0.05 was entered as 0.06). Subgroup analysis was conducted based on study methodology (study design, location, study setting and quality assessment ratings) and intervention factors (intervention strategies, type of vegetable, outcome measurements, delivered by and the intervention recipient).…”
Section: Gripshover Andmentioning
confidence: 99%
“…If past lab studies generalize, parents may be able to covertly increase consumption of healthy foods by adjusting fruit and vegetable portions while reducing or holding entrée size constant (Kral et al 2010;Mathias et al 2012;Savage et al 2012). Other covert possibilities include serving vegetables at a meal, adding pureed vegetables to entrees, or substituting ingredients to reduce calories --these can be effective because both adults and children tend to eat the same weight of food even when calories have been reduced (Leahy et al 2008;Spill et al 2010Spill et al , 2011.…”
Section: Creating a Healthy Home Environmentmentioning
confidence: 99%
“…vegetable soup) (73,74) or larger portions of fruit and vegetables with a meal (75,76) , were effective strategies in both promoting fruit and vegetable intake and decreasing the ED of children's meals. For example, in the study by Kral et al (75) when the PS of the broccoli and carrots side dish was doubled (75 g v. 150 g), children consumed significantly less of the pasta entree.…”
Section: Additive Effects Of Portion Size and Energy Density On Energmentioning
confidence: 99%